A relação entre a desigualdade em termos do IDH-M e as Taxas de Homicídios no município de São Paulo - Alvarenga, Bruno (Argumentum, 2020)
Since the end of the 1990s, there has been an increase in the homicide rate in Brazil, however, in the state of São Paulo, mainly in its capital, this indicator is out of step with the country and the other Federation Units and their Capitals. In spite of the multifactorial characteristic of the phenomenon, the purpose of this article is to look at the homicide rate in the city of São Paulo from the perspective of the HDI-M of its Administrative Districts between the years 2000 and 2010, through statistical analysis descriptive, spatial exploratory and bibliographic review. There are signs that the reduction of inequality in terms of HDI-M may have influenced the drop in the homicide rate in the municipality of São Paulo.